Implementasi Kurikulum Merdeka pada Perkembangan Anak Usia Dini di TK IT Menara Fitrah - Mareta, Sisiliya; Juniarni, Cittra; Muharrahman; Darda, Abu; Irbah, Ariq Nurjannah (Jurnal I TIBAR, 2025)
This research aims to analyze the implementation of the Merdeka Curriculum at the IT Tower Fitrah Kindergarten in an effort to support the development of aspects of early childhood development. The Merdeka Curriculum, which is designed to provide flexibility to educators in designing learning based on children's potential, needs and interests, has been implemented at the Tower Fitrah IT Kindergarten since the 2024 school year. This research uses a qualitative approach with a case study method. Data was obtained through interviews with teachers, observation of learning activities, and curriculum program documentation.The research results show that the implementation of the Merdeka Curriculum at the Tower Fitrah IT Kindergarten has been implemented through various strategies, such as integrating project-based learning, using innovative learning media, and strengthening parental involvement in the learning process. Apart from that, a personal approach to each child can increase children's learning motivation, creativity and social skills. However, several challenges were also identified, including a lack of in-depth teacher training regarding the Independent Curriculum and limited learning support facilities.This research concludes that the Merdeka Curriculum has had a positive impact on the development of early childhood at the IT Tower Fitrah Kindergarten, however, it is necessary to strengthen the aspects of teacher training and provide supporting facilities to optimize implementation. The recommendation of this research is to increase collaboration between schools, parents and the government to support the continued implementation of the Independent Curriculum.